Modeling and controller design of pneumatic actuator system with control valve [electronic resource] - Norizam Mohamed Yusoff, 1976- (2013)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2013